Study Of Tourism Suitability And Ecological Carrying Capacity Of Minang Rua Beach In South Lampung District As An Ecotourism Destination - Doni Widyasmoro; Hari Kaskoyo; Abdullah Aman Damai; Nur Efendi; Endro Prasetyo Wahono (Journal of Tropical Marine Science, 2025)
Tourism suitability analysis is important to determine the suitability of an area for beach recreation according to its ecological carrying capacity. This study aims to analyze the suitability and carrying capacity of the ecotourism area at Minang Rua Beach, South Lampung Regency, Lampung Province. Data collection of physical parameters of the beach was carried out using the field observation method. Data were analyzed using the tourism suitability index and area carrying capacity. The results showed that the ecotourism suitability index for beach recreation at Minang Rua Beach at station 1 was 2.875, at station 2 was 3.000, and at station 3 was 2.430. The level of suitability for beach recreation at Stations 1 and 2 was categorized as very suitable (S1), while at Station 3 was categorized as suitable (S2). The carrying capacity of the area at Minang Rua Beach for beach recreation activities at Station 1 was 119 people/day, at Station 2 was 364 people/day and at Station 3 was 158 people/day. The managers of this area are expected to be able to implement tourism activities according to their ecological carrying capacity so that their sustainability can be maintained.